A mosaic of wings : a novel - Duffy, Kimberly (Bethany House Publishers, 2020)
"In 1885, determined to uphold her father's legacy, Nora Shipley joins an entomology research expedition to India. In this spellbinding new land, Nora is torn between saving a young Indian girl and saving her career, and between what she's always thought she wanted and the man she's come to love"--